The role and therapeutic potential of gut microbiome in severe burn - Huang, Zhijie; Huang, Yisheng; Chen, Jun; Tang, Zhengming; Chen, Yuanxin; Liu, Hongyu; Huang, Mingshu; Qing, Ling; Li, Li; Wang, Qin; Jia, Bo (Frontiers in Cellular and Infection Microbiology, 2022)
Severe burn is a serious acute trauma that can lead to significant complications such as sepsis, multiple organ failure, and have a high mortality worldwide. The gut microbiome, as the largest microbial reservoir in the human body, plays a major role in this pathogenic process. Intestinal dysbiosis and disruption of the intestinal mucosal barrier are common after severe burn, leading to bacterial translocation to bloodstream and other organs of the body, which is associated with many subsequent severe complications. The progression of some intestinal diseases can be improved by modulating the composition of gut microbiota and the levels of its metabolites, which also provides a promising direction for post-burn treatment. In this article, we summarized the studies describing changes in the gut microbiome after severe burn, as well as changes in the function of the intestinal mucosal barrier. Additionally, we presented the potential and challenges of the microbial therapy, which may provide the microbial therapy strategies for the severe burn.